MILITARY AND SECURITY EDUCATION FOR REGIONAL CO-OPERATION : A CASE STUDY OF THE SOUTHERN AFRICAN DEFENCE AND SECURITY MANAGEMENT NETWORK - Cawthra, Gavin (Scientia Militaria - South African Journal of Military Studies, 2020)
This article first summarises approaches to military and security education at tertiary levels for officers and senior security officials, identifying some institutional and conceptual issues, before moving on to a fairly detailed case study of the Southern African Defence and Security Management Network (SADSEM). In its institutional form, from 2000 to 2010, SADSEM was a unique experiment in building a regional network of universities providing training and education in security studies, promoting regional security co-operation and integration and working closely with security forces and governments in the Southern African region. Although it mostly worked in English, it also carried out education and research in French and Portuguese, established an institutional base in ten Southern African Development Community (SADC) nations and delivered programmes in all the then 15 of them. Its activities included providing training and education for defence and security management, civil-military relations, peacekeeping and peacebuilding, policy support and the building of scholarly capacity though regional co-operation. Today SADSEM activities are restricted mainly to an annual security review conference, but its real legacy is in the institutions and capacities it built within several Southern African countries, although not all survive. SADSEM kept a low profile because of extreme sensitivities in Southern Africa around security issues, and this is the first attempt to examine its experience in the context of higher-level security education and training.